KRIMINALISASI TERHADAP KORPORASI YANG TIDAK VALID DALAM MELAPORKAN PEMILIK KEUNTUNGANNYA (BENEFICIAL OWNERSHIP) - Pratama, Restu Ananda; Erdianto, Erdianto; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Presidential Regulation Number 13 of 2018 concerning the Principle of RecognizingBeneficial Owners of Corporations in the Context of Preventing Crimes of MoneyLaundering and Terrorism Financing is the highest legal umbrella for implementing theprinciple of recognizing beneficial ownership in Indonesia today. Reporting data onbeneficial owners of a corporation is mandatory, so data validation is a very crucial thing todo. In this presidential regulation, only matters of an administrative nature are regulated andno threat sanctions have been regulated as a means of prevention and providing a deterrenteffect to every perpetrator of violations in terms of validating data on the beneficial ownersof a corporation.This research is normative legal research supported by secondary data,carried out by using library materials as the main focus. Also called doctrinal legal research,namely legal research that uses data based on library research by taking quotations fromreading books, or supporting books that are related to the problem to be researched. Thus,this research uses secondary data sources consisting of primary, secondary and tertiary legalmaterials. This research also uses qualitative data analysis and produces descriptive data.From the results of the discussions and research carried out, several conclusionswere obtained, namely: First, the regulation regarding Reporting of Beneficial Owners of aCorporation is regulated by Presidential Regulation Number 13 of 2018. In terms of law-making procedures, a Presidential Regulation is not justified in containing criminalprovisions , because there is a principle of No Punishment Without Representatives, criminalprovisions are only included if the Regulation is issued by the Legislative Body. Second,criminalization must be created through legality which will be included later in a new law,raising the level of the Presidential Regulation to a law which contains provisions forimprisonment and fines which are prepared taking into account the outlook on life,awareness and legal ideals, as well as philosophy. the Indonesian nation which originatesfrom Pancasila and the Preamble to the 1945 Constitution of the Republic of Indonesia.Keywords: Criminalization - Corporation – Beneficial Owner